Experimental and theoretical study on two types of shape memory alloy devices. - Li, Hui
This study proposes two types of shape memory alloy (SMA)-based devices, the tension SMA device (TSD) and the scissor SMA device (SSD), for the increase of stiffness. Both devices employ superelastic NiTi wires with a diameter of 1.2 mm. Performance tests to study pseudoelastic behavior of NiTi wires find that NiTi wire's pseudoelastic property is insensitive to loading frequency within the meaningful frequency range of most structures in civil engineering. The detailed design of TSD and SSD using NiTi wire is then presented accordingly. Shaking table tests of a scaled 5 story steel frame incorporated with TSDs and SSDs, respectively, in the first story are carried out. The experimental results indicate that both SMA devices can effectively reduce building seismic response. SSDs achieve greater response reduction than TSDs due to their displacement magnification configuration. The seismic response of the building model with and without SMD devices is numerically simulated and the simulation results demonstrate that they are in good agreement with the experimental results. Finally, it is identified that by using the wavelet transform method the structures incorporated with SMA devices exhibit nonlinear behavior and the time dependent characteristics of natural frequency during earthquake excitation.
Keywords: SMA; Pseudoelasticity; Seismic; Stiffness; Experiment and simulation; Time-frequency analysis; Damage; Nonlinearity